The role of Public Relations in Managing International Conferences: A Field Study on a Sample of Sulaymaniyah University Lecturers - صابر محمد سعید, لانه; شهاب مارف, چرۆ (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
This research aims to identify the roles played by public relations in managing international conferences. This research is descriptive research and the field survey method was used for a non-random, intentional sample of (43) lecturers from the College of Humanities at the University of Sulaimani. The research reached several conclusions, the most important of which are: Professors of the University of Sulaimani believe that before holding a conference, coordination must be made with the presidencies of universities, institutes and academic departments. The respondents believe that choosing appropriate slogans is one of the main tasks of the coordination and preparation committees for international conferences. The research sample attended more than one meeting with the conference initiator to discuss the main ideas. Faculty members at the University of Sulaimani were aware of all meetings with the conference sponsors and participated in them. The study sample attended more than one meeting to determine the main and sub-committees of the conference. The conference budget was estimated with the initiating party in a transparent and thoughtful manner.